2021
DOI: 10.1002/ehf2.13255
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenia in heart failure: a systematic review and meta‐analysis

Abstract: Aims Sarcopenia has been found to be frequently associated with co-morbidity among patients with heart failure (HF). However, there remain insufficient data to accurately estimate the global prevalence of sarcopenia in HF. Therefore, the purpose of this research was to conduct a systematic review and meta-analysis to estimate the current overall prevalence of sarcopenia in patients with HF. Methods and results We searched relevant databases for studies published up to 13 July 2020, assessing sarcopenia in vpat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
95
1
17

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(121 citation statements)
references
References 39 publications
8
95
1
17
Order By: Relevance
“…Even more important, early initiation of EMS may prevent additional muscle wasting during hospitalisation in patients with HF with high prevalence of sarcopenia and frailty and may also increase their acceptance of recommendations for cardiac rehabilitation. [30][31][32] In our study, even a short-term EMS course was sufficient to increase 6-MWTD and to improve QoL corresponding with previous reports. [20][21][22] Immediate beneficial effects of EMS are observed even after a single session which might partly be explained by peripheral vasodilation and better muscle perfusion.…”
Section: Heart Failure and Cardiomyopathiessupporting
confidence: 89%
See 1 more Smart Citation
“…Even more important, early initiation of EMS may prevent additional muscle wasting during hospitalisation in patients with HF with high prevalence of sarcopenia and frailty and may also increase their acceptance of recommendations for cardiac rehabilitation. [30][31][32] In our study, even a short-term EMS course was sufficient to increase 6-MWTD and to improve QoL corresponding with previous reports. [20][21][22] Immediate beneficial effects of EMS are observed even after a single session which might partly be explained by peripheral vasodilation and better muscle perfusion.…”
Section: Heart Failure and Cardiomyopathiessupporting
confidence: 89%
“…Even more important, early initiation of EMS may prevent additional muscle wasting during hospitalisation in patients with HF with high prevalence of sarcopenia and frailty and may also increase their acceptance of recommendations for cardiac rehabilitation. 30–32 …”
Section: Discussionmentioning
confidence: 99%
“…The cardiovascular involvement usually has the potential to extend into the post-COVID-19 recovery period, with the possibility of further interfering with the skeletal muscle [15,74]. On the other hand, the COVID-19 may develop in a patient already burdened with cardiovascular disease and thus prone to the development of sarcopenia [75]. In such case the pro-sarcopenic effects of COVID-19 would act synergistically with the burden already present [76].…”
Section: The Effect Of the Cardiovascular Involvement On The Development Of Sarcopenia Is Complexmentioning
confidence: 99%
“…low muscle mass and function) may differ according to the diagnostic criteria used, recent pooled analyses revealed that these conditions are highly prevalent among community‐dwelling 3 and hospitalized older adults 4 as well as patients with lung diseases, 5 liver cirrhosis, 6 cancer, 7 and other diseases. 8 , 9 , 10 Patients may also lose muscle in the presence of obesity (i.e. sarcopenic obesity) or without changes in body weight.…”
Section: Introductionmentioning
confidence: 99%